Defecation Site Preferences and Spatial Ecological Segregation of Forest Musk Deer and Siberian Roe Deer in North China - Yixin Li; Luyao Hai; Pengfei Luo; Wangshan Zheng; Xuelin Jin; Jiangcheng Liu; Haiyan Wang; Defu Hu (Animals)
The forest musk deer (Moschus berezovskii) and Siberian roe deer (Capreolus pygargus) are browsers with a broad sympatric distribution in North and Southwest China. However, little is known about their spatial utilization of microhabitats and habitats. This study, conducted on Huanglong Mountain in China, analyzed the defecation site distribution, indicating preferences of forest musk deer and Siberian roe deer for their habitat demands. Using generalized linear mixed models (GLMMs), we compared the defecation site preferences of both species and further examined their spatial utilization patterns. The results indicated that the primary factors influencing defecation site preferences for forest musk deer were slope (15.79%), elevation (4.26%), herbaceous cover (19.93%), herb height (33.73%), and tree diversity (15.64%). Conversely, for Siberian roe deer, elevation (54.63%) and herbaceous cover (29.31%) were the key factors. Significant differences were found in elevation (p < 0.001) and herbaceous diversity (p < 0.01) between the defecation sites of the two species, with additional notable differences in slope position, tree diversity, and average tree height (p < 0.05). Furthermore, forest musk deer primarily utilized broadleaf forests, coniferous forests, mixed conifer-broadleaf forests, and sparse woodlands. In contrast, Siberian roe deer utilized broadleaf forests, sparse woodlands, and coniferous forests, showing a significant difference (p = 0.01). These findings suggest distinct spatial ecological segregation between forest musk deer and Siberian roe deer regarding their microhabitat preferences and vegetation type utilization at the habitat scale.